Cold turkey or gradual approach for smoking cessation?. Issue 1 (January 2017) - Miller, Deborah
Abstract : N/A: Lindson‐Hawley N, Banting M, West R, et al. Gradual versus abrupt smoking cessation: a randomized, controlled noninferiority trial. Ann Intern Med . 2016; 164(9):585–592.